2012
DOI: 10.1021/cm3003063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Micrometer Length Indium Sulfide Nanosheets and Study of Their Dopant Induced Photoresponse Properties

Abstract: Synthesis of various nanostructured semiconductor materials and processing them for different device fabrications has been at the forefront of research for the last two decades. In comparison to spherical nanoparticles, anisotropic materials e.g. nanorods, nanowires, and nanodisks have been widely explored to obtain a better performance of the devices. In addition, it is also well-known that nanomaterials, on doping with suitable impurities, can enhance the device sensitivity and speed. Combining both, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 45 publications
4
70
0
Order By: Relevance
“…The simulated MoirØ pattern from the FFT is also been shown in Figure 3 Although MoirØ fringes are very common and are supposed to be obtained at the overlapping regions of two sheets or platelets, we observed here practically the same with several interesting patterns. To our knowledge, the case here is unique among previous reports on MoirØ fringes [28,[36][37][38] and we assume this to be because of the highly crystalline nature of the platelets. It has been observed that these platelets are associated with several important and useful materials properties.…”
mentioning
confidence: 51%
“…The simulated MoirØ pattern from the FFT is also been shown in Figure 3 Although MoirØ fringes are very common and are supposed to be obtained at the overlapping regions of two sheets or platelets, we observed here practically the same with several interesting patterns. To our knowledge, the case here is unique among previous reports on MoirØ fringes [28,[36][37][38] and we assume this to be because of the highly crystalline nature of the platelets. It has been observed that these platelets are associated with several important and useful materials properties.…”
mentioning
confidence: 51%
“…It has been reported that In 2 S 3 may substitute highly toxic cadmium sulfide (CdS) in the buffer layer of chalcogenide-type solar cells [26,27]. For these reasons, In 2 S 3 was selected as the buffer layer for CIS-photosensitized TNAs in this work.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Due to its intrinsic defect structure, b-In 2 S 3 shows interesting electronic [3], optical [1,4], acoustic [5] optoelectronic and semiconductor sensitization [6] properties. In 2 S 3 is one of the potential materials that can be used for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 2 S 3 is one of the potential materials that can be used for many applications. This includes it as a potential substitute of toxic CdS buffer layer in solar cells [7][8][9][10] and has been used in heterojunction in photovoltaic electric generators [10], as a photocatalytic material for hydrogen production [11], in biological imaging sensors [12], as a photodetector [13], a photocatalytic material for the degradation of dyes [14][15][16][17], in photoelectrochemical solar cells [18] and water splitting [19]. This is mainly due to its chemical stability, wide energy band gap, and controllable electrical properties [20].…”
Section: Introductionmentioning
confidence: 99%